Comparison of enteral ethanol and benzodiazepines for alcohol withdrawal in neurocritical care patients. (September 2016) - Gipson, Gregory; Tran, Kim; Hoang, Cuong; Treggiari, Miriam
Highlights: No significant difference in worsening of alcohol withdrawal severity was observed in the first 24 hours between groups treated with benzodiazepines or enteral ethanol. Benzodiazepine treated patients displayed higher maximal alcohol withdrawal severity scores in the first 5 days of study. Patients treated with enteral ethanol had shorter hospital lengths of stay by 1 day, p = 0.02. Study groups differed by mortality risk with the ethanol group appearing less severely ill. The utility of benzodiazepines compared to enteral ethanol continues to remain unclear for this population. Abstract: We designed a study to evaluate the use of benzodiazepines and ethanol in patients being assessed for alcohol withdrawal and compare outcomes between the two agents. This is a retrospective chart review of patients admitted to neurocritical care or neurosurgical services who were at risk for ethanol withdrawal between June 2011 and September 2015. Patients were divided into two groups based on the first medication administered for alcohol withdrawal management, either benzodiazepine (n = 50) or enteral ethanol (n = 50). The primary endpoint was the maximum change in Clinical Institute Withdrawal Assessment of Alcohol scale (CIWA) score within the first 24 hours. Secondary endpoints included maximum and minimum CIWA score in 5 days, length of stay, and change in Glasgow Coma Scale. Study groups differed by mortality risk, level of coma at admission, and other clinical characteristics, with the ethanol group appearing less severely ill. There was no significant difference between the two groups in the maximum change in CIWA score at 24 hours (−0.97, 95%CI: −3.21 to 1.27, p = 0.39). Hospital and intensive care unit length of stay was 6.5 days and 1 day shorter for the ethanol group (p = 0.03 and p = 0.02, respectively). In summary, enteral ethanol was preferentially used in patients who are more likely to be capable of tolerating oral intake. We found that the change from baseline in CIWA score or other physiologic variables was not substantially different between the two agents. The overall utility of benzodiazepines and enteral ethanol remains unclear for this population and further study is needed to determine superiority.